"Death is a disease": Cryopreservation, neoliberalism, and temporal commodification in the U.S. (August 2018) - Genovese, Taylor R.
Highlights: Cryopreservation can be better understood as the physical embodiment of neoliberalism. Cryopreservation can further be described as a 21st century Durkheimian, Americanist death ritual. These engagements can be described as being part of the cryonic assemblage.